2019
DOI: 10.3389/fmicb.2019.02212
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Co-inhabiting Coagulase Negative Staphylococci on S. aureus agr Quorum Sensing, Host Factor Binding, and Biofilm Formation

Abstract: Staphylococcus aureus is a commensal colonizer of both humans and animals, but also an opportunistic pathogen responsible for a multitude of diseases. In recent years, colonization of pigs by methicillin resistant S. aureus has become a problem with increasing numbers of humans being infected by livestock strains. In S. aureus colonization and virulence factor expression is controlled by the agr quorum sensing system, which responds to and is activated by self-generated, autoinducing peptides (AIPs). AIPs are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 62 publications
2
38
0
1
Order By: Relevance
“…The agr locus consists of four genes: agrB encodes a membrane protein responsible for translocation and modification of AgrD; agrD encodes an AIP precursor octapeptide; agrC encodes a membrane receptor protein of the AIP signal and agrA encodes the AgrA response regulator that activates transcription. agr varies between S. aureus strains and can be divided into four groups (agr type I, II, III and IV) [70]. Studies have reported the association between the agr types and the different clonal lineages, antibiotic resistance profile, biofilm formation, the toxins produced and their link with diseases [71].…”
Section: Accessory Gene Regulator (Agr) Typingmentioning
confidence: 99%
See 2 more Smart Citations
“…The agr locus consists of four genes: agrB encodes a membrane protein responsible for translocation and modification of AgrD; agrD encodes an AIP precursor octapeptide; agrC encodes a membrane receptor protein of the AIP signal and agrA encodes the AgrA response regulator that activates transcription. agr varies between S. aureus strains and can be divided into four groups (agr type I, II, III and IV) [70]. Studies have reported the association between the agr types and the different clonal lineages, antibiotic resistance profile, biofilm formation, the toxins produced and their link with diseases [71].…”
Section: Accessory Gene Regulator (Agr) Typingmentioning
confidence: 99%
“…Studies have reported the association between the agr types and the different clonal lineages, antibiotic resistance profile, biofilm formation, the toxins produced and their link with diseases [71]. For instance, agr type I and II strains are usually associated with endocarditis and septicemia whereas agr type III and IV strains are associated with TSST-1, exfoliative syndromes and bullous impetigo [70].…”
Section: Accessory Gene Regulator (Agr) Typingmentioning
confidence: 99%
See 1 more Smart Citation
“…Each agr type specifically responds to its cognate AIP signal, and intraspecies cross talk between noncognate S. aureus agr types has been extensively characterized (30). Furthermore, there are now several examples of human-and animal-derived CoNS AIPs that inhibit S. aureus quorum sensing via interspecies cross talk (12,(31)(32)(33)(34). For example, quorum sensing interference by the rare skin commensal Staphylococcus caprae attenuated acute MRSA skin infection and also limited initial MRSA skin colonization (11).…”
mentioning
confidence: 99%
“…Бурцева, М.А. Сергеева на у S. lugdunensis [25], губительно действующих на S. aureus, эти виды (S. epidermidis и S. caprae) могут подавлять «чувство кворума» и агрессию золотистого стафилококка, в том числе за счет неродственных аутоиндуцирующих пептидов [26,27,28]. Важными считаются выработка толерантности иммунитета к стафилококкам постоянными и разнообразными компонентами микробиома (S. epidermidis и другие комменсалы) начиная с первых лет жизни, а также «тренировка» особых иммунокомпетентных клеток в зрелом возрасте, способствующая, в том числе, образованию противомикробных пептидов [29].…”
Section: стафилококки как часть микробиома кожи человекаunclassified